Benefit of Adding Ezetimibe to Statin Therapy on Cardiovascular Outcomes and Safety in Patients With Versus Without Diabetes Mellitus: Results From IMPROVE-IT (Improved Reduction of Outcomes: Vytorin Efficacy International Trial) - Giugliano, Robert P; Cannon, Christopher P; Blazing, Michael A; Nicolau, José C; Corbalán, Ramón; Špinar, Jindřich; Park, Jeong-Gun; White, Jennifer A; Bohula, Erin A; Braunwald, Eugene; IMPROVE-IT (Improved Reduction of Outcomes: Vytorin Efficacy International Trial) Investigators (Circulation, 2018)
BACKGROUND: Ezetimibe, when added to simvastatin, reduces cardiovascular events after acute coronary syndrome. We explored outcomes stratified by diabetes mellitus (DM). METHODS: In IMPROVE-IT (Improved Reduction of Outcomes: Vytorin Efficacy International Trial), 18 144 patients after acute coronary syndrome with low-density lipoprotein cholesterol 50 to 125 mg/dL were randomized to 40 mg ezetimibe/simvastatin (E/S) or 40 mg placebo/simvastatin. The primary composite end point was cardiovascular death, major coronary events, and stroke. DM was a prespecified subgroup. RESULTS: The 4933 (27%) patients with DM were more often older and female, had had a prior myocardial infarction and revascularization, and presented more frequently with non-ST segment elevation acute coronary syndrome compared with patients without DM (each P<0.001). The median admission low-density lipoprotein cholesterol was lower among patients with DM (89 versus 97 mg/dL, P<0.001). E/S achieved a significantly lower median time-weighted average low-density lipoprotein cholesterol compared with placebo/simvastatin, irrespective of DM (DM: 49 versus 67 mg/dL; no DM: 55 versus 71 mg/dL; both P<0.001). In patients with DM, E/S reduced the 7-year Kaplan-Meier primary end point event rate by 5.5% absolute (hazard ratio, 0.85; 95% confidence interval, 0.78-0.94); in patients without DM, the absolute difference was 0.7% (hazard ratio, 0.98; 95% confidence interval, 0.91-1.04; Pint=0.02). The largest relative reductions in patients with DM were in myocardial infarction (24%) and ischemic stroke (39%). No differences in safety outcomes by treatment were present regardless of DM. When stratified further by age, patients ≥75 years of age had a 20% relative reduction in the primary end point regardless of DM (Pint=0.91), whereas patients <75 years of age with DM had greater benefit than those without (Pint=0.011). When stratified by the TIMI (Thrombolysis in Myocardial Infarction) Risk Score for Secondary Prevention, all patients with DM demonstrated benefit with E/S regardless of risk. In contrast, among patients without DM, those with a high risk score experienced a significant (18%) relative reduction in the composite of cardiovascular death, myocardial infarction, and ischemic stroke with E/S compared with placebo/simvastatin, whereas patients without DM at low or moderate risk demonstrated no benefit with the addition of ezetimibe to simvastatin (Pint =0.034). CONCLUSIONS: In IMPROVE-IT, the benefit of adding ezetimibe to statin was enhanced in patients with DM and in high-risk patients without DM. CLINICAL TRIAL REGISTRATION: URL: https://www.clinicaltrials.gov. Unique identifier: NCT00202878.
Keywords: biologické markery; Risk Assessment; komorbidita; lidé; Dyslipidemias; výsledek terapie; Middle Aged; Risk Factors; LDL-cholesterol; diabetes mellitus; Female; Ezetimibe, Simvastatin Drug Combination; Hydroxymethylglutaryl-CoA Reductase Inhibitors; hodnocení rizik; Humans; Diabetes Mellitus; Comorbidity; acute coronary syndromes; lidé středního věku; Biomarkers; dyslipidemie; mužské pohlaví; Cholesterol, LDL; ezetimibe; statiny; Time Factors; kombinace léků ezetimib a simvastatin; ženské pohlaví; Acute Coronary Syndrome; Treatment Outcome; časové faktory; akutní koronární syndrom; Aged; Male; lipids; rizikové faktory; senioři